PENGARUH RETURN ON ASSET DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PT MAYORA INDAH Tbk PERIODE 2014-2023 - Firdaus, Moch Rizik; Watiningsih , Ferdina (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
. This study aims to determine the effect of Return on Assets and Debt to Equity Ratio on Stock Prices at PT Mayora Indah Tbk for the period 2013-2024. The research method used is quantitative. The data analysis used in this study includes descriptive statistical analysis, classical assumption tests, multiple linear regression, determination coefficient tests, and hypothesis tests (t-test and F-test). The results of this study indicate that, partially, Return on Assets does not have a significant effect on Stock Prices based on the results of the t-value of 0.304 < 2.365 with a significance value of 0.770 > 0.05. The Debt to Equity Ratio does not have a significant effect on Stock Price based on the results of the Thitung value of 2.165 < 2.365 with a significance of 0.067 > 0.05. Simultaneously, Return on Assets and Debt to Equity Ratio do not have a significant effect on Stock Price. This is evidenced by the F-value of 2.781 < 4.47 with a significance level of 0.129 > 0.05.